Implementation of topology converter into UM JaNetSim / Andrew Chiam Ming Jer - Andrew, Chiam Ming Jer (2004)
This project describes and implement the approach and procedure involve in the development of the network topology converter to be implemented in JaNetSim.The development of topology converter will made possible the conversion of different topology file format in Ns-2 and JaNetSim to enable wider range of simulation to be carried out more efficiently and effectively. Ns-2 is an established network simulator with the most active research and it can be a great and powerful reference tools to improve and complement the functionality of UM JaNetSim. The topology converter will incorporate several important features. The most important features lies in the object oriented approach which provide the luxurious of manipulating inheritance and polymorphism which provide benefits like reusability, flexibility and extendibility. Another important feature is the friendly, intuitive and simple to use interface. The interface provided by the topology converter will be consistent with the JaNetSim layout. This will greatly cut the amount of time to help user to familiarize and utilize the functionalities provided by the topology converter. The topology converter will be helpful to translate various topology formats to increase portability and widen the scope for various simulators.